Kemampuan Komunikasi Interpersonal Mahasiswa Yang Mengikuti PLP 2 - Nurfajri, Muhammad Tawsy; Nurhasanah, Nurhasanah; Yahya, Martunis (Jurnal Suloh, 2022)
The Education Department of Syiah Kuala University implements two internship program series, PLP 1 and PLP 2. In such programs, students should have good communication skills. This study aims to describe the interpersonal communication skills of students who have participated in the school field introduction program (PLP2). This study uses a quantitative approach with a descriptive method. The research population was 40 Guidance and Counseling students of the Education Department of Syiah Kuala University with saturated sampling; that is, the entire population was the sample. The data collection technique used a Likerts model scale questionnaire, a descriptive percentage technique applied to analyse the data. The results showed that the description of interpersonal communication skills of students who had participated in the PLP 2 program was in the high category with a percentage of 47.5% (19 students), very high category 45% (18 students), moderate category 5% (2 students), and deficient category 2.5% (1 student). The description of interpersonal communication skills on openness and empathy is in the high category, with an average value percentage above 36.35%. The aspects of mutual support, positive feelings, and elements of equality are in the very high category with a percentage of the average value. The average is above 40.33% from a total sample of 40 students. The research concluded that the interpersonal communication skills of students who take part in PLP 2 are in the high category.Keywords: College Students, Interpersonal Communication, Internship.ABSTRAKKemampuan komunikasi interpersonal merupakan hal yang sangat dibutuhkan dalam layanan konseling, termasuk dalam pelaksanaan program pengenalan lapangan persekolahan (PLP2). Penelitian ini bertujuan untuk mengetahui gambaran kemampuan komunikasi interpersonal mahasiswa BK FKIP USK yang telah mengikuti program pengenalan lapangan persekolahan (PLP2). Penelitian ini menggunakan pendekatan kuantitatif dengan metode deskriptif. Populasi penelitian adalah 40 mahasiswa dengan pengambilan sampel jenuh yaitu seluruh populasi menjadi sampel. Teknik pengumpulan data menggunakan angket bentuk skala likert, data dianalisis menggunakan teknik deskriptif persentase. Hasil penelitian menunjukkan bahwa gambaran kemampuan komunikasi interpersonal mahasiswa BK FKIP USK yang telah mengikuti program PLP 2 berada pada kategori tinggi dengan persentase 47,5% (19 mahasiswa), kategori sangat tinggi 45% (18 mahasiswa), kategori sedang 5% (2 mahasiswa), dan kategori sangat rendah 2,5% (1 mahasiswa). Gambaran kemampuan komunikasi interpersonal pada aspek keterbukaan dan empati berada pada kategori tinggi dengan persentase nilai rata-rata diatas 36,35%, kemudian pada aspek sikap saling mendukung, aspek sikap perasaan positif, dan unsur kesetaraan berada pada kategori sangat tinggi dengan persentase nilai rata-rata di atas 40,33%, dari jumlah sampel sebanyak 40 orang mahasiswa. Dari itu dapat disimpulkan bahwa kemampuan komunikasi interpersonal mahasiswa BK FKIP USK yang mengikuti PLP 2 berada pada kategori tinggi.